Radioactive pollution of the Chernobyl cooling pond bottom sediments. II. Distribution of 137Cs, 241Am, 90Sr in a solid phase - L. S. Pirnach (Ядерна фізика та енергетика)
The second part of complex research of the Chernobyl cooling pond bottom sediments are presented Data about vertical distribution of radioactive pollution 137Cs, 241Am, 90Sr in a solid phase of sediments are received. Distribution coefficients 137Cs and 90Sr, selectivity coefficients of their exchange with similar cations and physical-chemical forms are defined. Results of research of radionuclide chemical recovery from the sediment samples are analyzed.